Artisanal Fishers Knowledge of Covid-19 and the Impact of Lock Down on Fishing in Igbomotoru Bayelsa State, Niger Delta - Sabina Alatari Ngodigha (East Asian Journal of Multidisciplinary Research, 2023)
The study was conducted with the aimed of identifying the impact of COVID-19 lock down on Artisanal Fishers and fishing operations. Data was collected through face-face interview. Fishers who had 15 years of fishing experience and above were involved in the research. Results showed that Fishers were well informed of COVID-19 pandemic. There was no case of COVID-19. Fishers could read and write as they had the basic primary education. Restriction on movement had major setback on the fishing operations of fishers and intermediaries given the low fish price and reduced movement of fish traders. Landings were very good during lock down. Poor before lock down dwindled down to good after the lock down due to human activities.